Variasi Kekencangan Mula (Pre-Tension) Satu Arah pada Reinforcement Fibre Panel Komposit terhadap Kekuatan Tarik - Oerbandono, Tjuk; Wardhana, Bayu Satriya; K., Praisy Meivy; Sonief, Achmad As’ad (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2014)
Composites consist of more than one type of material that is designed to get a combination of the best characteristics of each constituent components. This research was conducted to determine the effect of variations in one direction of the pre tension on reinforcement fibre to the tensile strength of composite panel. The produced composite composed of woven roving type E-glass fibres and polyester resin 108. The resulted composites were made by hand lay-up method. The applied pre tension variations in the experiment are 0N, 5N, 10N, 15N, and 20N. Tensile testing was done by using a universal tensile testing machine in accordance with ASTM D 3039. From the measurements known that the applied pre tension on reinforcement fibre influence the tensile strength of the composite. Variations of pre tension from F = 0 N up to F = 20 N showed that the composite’s tensile strength tend to increase. Reinforcement fibre without pre tension or F= 0 N has the lowest tensile strength value 235.33 N/mm2, while the highest tensile strength of composite 367.02 N/mm2 belong to the reinforcement fibre with one direction pre tension of 20 N.Keywords: Pre-Tension, Reinforcement Fibre, Composite Panel, Tensile Strength